Meningkatkan Hasil Belajar IPS Pokok Bahasan Koperasi Melalui Penerapan Model Pembelajaran Kooperatif Tipe Jigsaw pada Siswa Kelas IV SD Negeri 66 Kota Ternate - Sufri Saleh (Peneliti.net, 2021)
This study aims to determine the application of the jigsaw type of cooperative learning model in the social studies subject of cooperative materials to improve the learning outcomes of fourth grade students of SD 66 Ternate. This research was conducted using classroom action research methods. The research subjects were fourth grade students of SD Negeri 66 Ternate with 27 students. This research has been carried out in two cycles. The procedures in each cycle include the following stages: action planning, action implementation, observation and reflection. The effectiveness of the action in each cycle is measured from the results of observations and reading skills tests. Observational data are described, interpreted, then reflected to determine corrective actions in the next cycle. Meanwhile, the test results are analyzed by describing the test scores between cycles until the results can reach the specified completion limit, namely at least 80% of students can follow the lesson well and get a score of 65 or more as the limit for completion of learning outcomes. The results showed an increase in student learning outcomes starting from the beginning before the action where in the pre-cycle the number of students who were able to reach the KKM was 13 people, in the first cycle it became 16 people and the second cycle became 23 people as well as the average student test scores before the action. was 64.44 after the implementation of the first cycle increased to 68.88 and the last after the implementation of the second cycle it became 80.18. Based on the actions taken, it can be concluded that the application of social studies learning cooperative materials using the jigsaw type cooperative learning model can improve the learning outcomes of fourth grade students at SD Negeri 66 Ternate.